TRANSMISI KEBIJAKAN MONETER MELALUI JALUR KURS NEGARA EMERGING MARKET - Ade Novalina (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2017)
This study aims to analyze the contribution of the variables of interaction variable monetary policy transmission (EX, GDP, INV, EXCHANGE, INF). This study uses secondary data or time series of the first quarter of 2000 to the first quarter of 20114. The model of data analysis in this study is a model Autoregression Vector (VAR) and sharpened by analyzing Impulse Response Function (IRF) and the Forecast Error Variance Decomposition (FEVD ). The results of the analysis of VAR indicate that the variable past (t-1) contribute to the variable now well on the variable itself and other variables and of the estimation results turned out to have a mutual relationship between the variables in which all the variables of variable monetary policy transmission (EX, GDP, INV , EXCHANGE, INF) contribute to each other. The results of the analysis of IRF is known that the stability of the response of all variables are formed in the period of five or medium-term and long-term, where the response of other variables to change one variable show different variations both positive response to negative or vice versa, and there are variables that responya remain positive or remain negative on the short term to long term. Analysis FEVD shows the variables that contributed most to the variable itself both in the short, medium and long term as EX, INF, GDP, INV, EXCHANGE, while the other variables that have the greatest influence on the variable itself in the short term, medium and long term is the largest EXCHANGE influenced by INF, INV biggest influenced by EXCHANGE, the largest EX influenced by GDP. The results of the analysis of the interaction of monetary and fiscal policy to macroeconomic stability indicates that the transmission of monetary policy is effective in keeping inflation and macroeconomic stability in Indonesia.